Detection of Mycobacterium tuberculosis and Its Rifampicin Resistance by Automated Nucleic Acid Ampli fication Test - Klayut, Wiphat; Srisangngam, Sopa; Rudeeaneksin, Janisara; Boonchu, Supranee; Toonkomdang, Sarawut; Sangkitporn, Somchai; Phetsuksiri, Benjawan (Journal of Health Science of Thailand, 2018)
Tuberculosis remains a major health problem. Detection of Mycobacterium tuberculosis from clinical specimens is an important process to diagnose of the disease. A molecular testing that provides an accurate and is a faster than standard bacteriological cultures is used to combine with the conventional methods. Xpert MTB/RIF, a molecular testing that is endorsed by World Health Organization uses an automated real-time PCR machine called “GeneXpert” to simultaneous detection of M. tuberculosis and its rifampicin resistance directly from clinical specimens which offers a high sensitivity and specificity. This research aimed to study performance of Xpert MTB/RIF in the direct detection of M. tuberculosis and its rifampicin resistance comparing to standard culture methods and rifampicin susceptibility testing by liquid media. One hundred and forty of decontaminated sputum from routine TB laboratory service were used. After culturing, a remaining sample was analyzed by Xpert MTB/RIF. It was found that the sensitivity and specificity of Xpert MTB/RIF were 88.55% (116/131) and 100.0% (9/9), respectively compared with TB culture, and 87.5% (7/8) and 97.18% (69/71), respectively compared with liquid susceptibility testing. Therefore, we concluded that Xpert MTB/RIF was suitable to use for detection of M. tuberculosis and its rifampicin resistance in clinical specimens which was highly sensitive and require less detecting time fewer than 2 hours.